Pathomorphological Studies of Outbreaks of Avian Pathogenic Escherichia coli Infections in the Commercial Chicken - Thippani, Chandravathi; Vemuri, Rama Devi; Kokila, Satheesh (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Colibacillosis, caused by Escherichia coli, affects domestic and wild birds. The economic losses in industrial and subsistence poultry farms  were considerable due to high morbidity and mortality and higher costs of medical treatments. A total of 488 birds were examined, out  of which pathogenic Escherichia coli was found in 308 (63.11%) birds based on the biochemical, cultural, morphological and staining  characters and these were confirmed by the polymerase chain reaction (PCR). Clinically affected birds showed symptoms of dullness,  depression, disinclination to move, chest and beak resting on the ground with closed eyelids, loss of weight, weakness, ruffled feathers,  gasping and distended abdomen. The pathological gross lesions noticed were the congestion of all visceral organ, fibrinous pericarditis,  perihepatitis, air-sacculitis, peritonitis and salpingitis. The histopathology of effected lungs, air-sacs, pericardium, heart, liver and its  capsule and peritoneum showed fibrinous inflammation with infiltration of inflammatory cells. The study concluded that colibacillosis  was the cause of death of birds with typical gross and histopathological lesions in various outbreaks.
Keywords: Chicken; Colibacillosis; Escherichia coli; Gross lesion; Histopathology; PCR